Ridiculous! - Coleman, Michael (Michael J.), 1946-; Williamson, Gwyneth, 1965- (Wauwatosa, WI : Little Tiger Press, 1996)
Instead of hibernating with her parents, a young turtle decides to explore the winter world outside their shed.
Keywords: Turtles -- Juvenile fiction; Winter -- Juvenile fiction